Analysis of Uterine Myoelectrical Signals Before and Immediately After Artificial Rupture of Membranes - Çelik, Önder; Hasçalık, Şeyma; Tağluk, Emin (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: This study was planned to compare the myoelectrical signals generated by gravid rat uterus before and immediately after artificial rupture of membranes (ROM) and the relationship between the pathological states and myoelectrical activity. MATERIALS AND METHODS: The uterine myoelectrical signal recording was carried out on eight Wistar albino gravid rats. At 15th day of gestation bipolar electrodes were subserously implanted into the uterus. After the replacement of electrodes recording of the myoelectrical activity was conducted by the use of MP100 A-CE data acquisition system. Following the first recording, in each animal a 0.5 cm hysteroamniotomy was made in one of the amniotic sacs and subsequently myoelectrical activity was re-recorded. RESULTS: While some of the uterine contractions were regular but some others were not, depending on the subject. After the rupture of membranes the irregularity of contractions as well as the rate of infrequent spike potentials, probably result from ROM effects and pollute the uterine signal, have increased. CONCLUSIONS: Based on the obtained results, it seems that uterine electrical activity and thus the contractions significantly change immediately after ROM. The characterization of unusual uterine contractions following rupture of membranes can help the physicians in early diagnosis and management of ROM.